Cultural Representation of Dalits in Nepali Literature Written by Dalit and Non-Dalit Writers - Magarati, Shyam Lal; Sherpa, Rinju (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
The major objective of this paper is to explore the cultural representation of Dalits in Nepali literature written by both Dalit and non-Dalit writers. To meet its objective, Likhe (2073) by Sarad Paudel and Itihāsko Ek Paikā (The brave person in the history, 2066) by Ranendra Barali have been selected purposively as primary texts for analysis. Stuart Hall’s (1997) “discursive approach” has been used as an approach for textual analysis. The findings of the study concluded that both types of writers have raised the issue of class struggle commonly based on socio-cultural factors. Dalit characters in both novels live in poverty and miserable condition whereas non-Dalit characters are presented as dominant and in better conditions in society. Similarly, Likhe and Mansingh are presented as major characters whereas non-Dalit characters are given the minor roles. Dalit characters are presented as underprivileged whereas non-Dalits belong to privileged group of people in society. Both writers raise the issues of inter-caste and intra-caste untouchable practices equally. Finally the paper is significant due to the comparative study on the socio-cultural issue of Dalit community presented by Dalit and non-Dalit writers.